Cross-sectional study of aortic valve calcification and cardiovascular risk factors in older Danish men. Issue 19 (10th August 2021) - Khurrami, Lida; Møller, Jacob Eifer; Lindholt, Jes Sanddal; Urbonaviciene, Grazina; Steffensen, Flemming Hald; Lambrechtsen, Jess; Karon, Marek; Frost, Lars; Busk, Martin; Egstrup, Kenneth; Fredgart, Maise Høigaard; Diederichsen, Axel Cosmus Pyndt
Abstract : Objective: Aortic valve calcification (AVC) and coronary artery calcification (CAC) are predictors of cardiovascular disease (CVD), presumably sharing risk factors. Our objectives were to determine the prevalence and extent of AVC in a large population of men aged 60–74 years and to assess the association between AVC and cardiovascular risk factors including CAC and biomarkers. Methods: Participants from the DANish CArdioVAscular Screening and intervention trial (DANCAVAS) with AVC and CAC scores and without previous valve replacement were included in the study. Calcification scores were calculated on non-contrast CT scans. Cardiovascular risk factors were self-reported, measured or both, and further explored using descriptive and regression analysis for AVC association. Results: 14 073 men aged 60–74 years were included. The AVC scores ranged from 0 to 9067 AU, with a median AVC of 6 AU (IQR 0–82). In 8156 individuals (58.0%), the AVC score was >0 and 215 (1.5%) had an AVC score ≥1200. In the regression analysis, all cardiovascular risk factors were associated with AVC; however, after inclusion of CAC ≥400, only age (ratio of expected counts (REC) 1.07 (95% CI 1.06 to 1.09)), hypertension (REC 1.24 (95% CI 1.09 to 1.41)), obesity (REC 1.34 (95% CI 1.20 to 1.50)), known CVD (REC 1.16 (95% CI 1.03 to 1.31)) and serum phosphate (REC 2.25 (95% CI 1.66 to 3.10) remained significantly associated, while smoking, diabetes, hyperlipidaemia, estimated glomerular filtration rate and serum calcium were not. Conclusions: AVC was prevalent in the general population of men aged 60–74 years and was significantly associated with all modifiable cardiovascular risk factors, but only selectively after adjustment for CAC ≥400 AU. Trial registration number: NCT03946410 and ISRCTN12157806 .